Efektivitas Video Edukasi Terhadap Peningkatan Pengetahuan Ibu tentang Gizi Seimbang pada Balita - Nafilah, Nafilah; Eliyana, Eliyana (Jurnal Ilmiah STIKES Yarsi Mataram, 2025)
The prevalence of stunting in Indonesia still leaves much to be done and requires the attention of all stakeholders. Various efforts have been made to eliminate factors that have the potential to trigger stunting, one of which is maternal knowledge. Educational efforts are being made to increase mothers' understanding of the importance of a balanced diet for young children. Knowledge can be increased in several ways. One of them is to provide education through video media, which is believed to be more easily accepted and understood by mothers. This study aims to improve mothers' understanding of balanced infant feeding through educational videos. The quasi-experimental pretest-posttest research design involved 20 mothers of young children. The data were then analyzed using the Wilcoxon test. The results of this study indicate that there is a significant increase in maternal knowledge about balanced feeding. This can be seen from the pretest mean of 6.4 ± 0.3 while the posttest mean is 9.3 ± 0.2 with p = 0.00. Educating mothers with videos has proven to be effective in increasing their knowledge about balanced nutrition. The use of audiovisual media is able to optimize the reception of information because it involves more than one sense of the body. It is expected that education of mothers can be done on an ongoing basis using more interactive and dynamic media. ABSTRAK revalensi angka stunting di Indonesia masih menyisakan banyak pekerjaan yang memerlukan perhatian seluruh pihak. Berbagai upaya dilakukan untuk mengeliminasi faktor yang berpotensi memicu stunting, salah satunya ialah pengetahuan ibu. Upaya edukasi dilakukan untuk meningkatkan pemahaman ibu tentang pemenuhan gizi yang seimbang untuk balita. Peningkatan pengetahuan dapat dilakukan dengan berbagai cara. Salah satunya adalah pemberian edukasi melalui media video yang diyakini dapat lebih mudah diterima dan dipahami oleh ibu. Penelitian ini bertujuan untuk meningkatkan pemahaman ibu tentang gizi seimbang pada balita melalui video edukasi. Desain penelitian quasi eksperimen dengan pretest-postest grup melibatkan sebanyak 20 ibu balita. Data kemudian dianalisis dengan menggunakan uji wilcoxon. Hasil penelitian ini menunjukkan terdapat peningkatan signifikan pengetahuan ibu tentang gizi seimbang. Hal ini terlihat dari hasil mean pretest sebesar 6.4±0.3 sedangkan mean postest sebesar 9.3±0.2 dengan p=0.00. Pemberian edukasi menggunakan video terbukti efektif dalam meningkatkan pengetahuan ibu tentang gizi seimbang. Penggunaan media audio visual mampu mengoptimalkan penerimaan informasi karena melibatkan lebih dari satu indra tubuh. Diharapkan pemberian edukasi pada ibu dapat dilakukan secara berkesinambungan dengan menggunakan media yang lebih interaktif dan dinamis.